Reactive Arthritis Following COVID-19 Vaccination: Report of Three Cases - Tasgöz, Cemre; Acar, Emre Ali; Sülükcü, Seref; Uslu, Sadettin; Gündüz, Ozgül Soysal (Aktuelle Rheumatologie, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the coronavirus disease 19 (COVID-19) pandemic, which has affected the entire world. The development of COVID-19 vaccines has helped to slow the spread of the virus. However, as with vaccines against other infectious diseases, adverse events can occur with COVID-19 vaccines. Here we present 3 cases of acute arthritis following COVID-19 vaccination and a comprehensive review of the existing literature.
Keywords: SARS-CoV-2; COVID-19; vaccine; reactive arthritis